PERCEPTIONS OF SERVICE PROVIDERS FOR PEOPLE LIVING WITH HIV/AIDS ON CHALLENGES THEY FACE WHILE PROVIDING SERVICES - Irida Agolli Nasufi; Marinela Sota (European Scientific Journal, ESJ, 2015)
This study aims to analyze the perceptions of service providers related to services provided for people with HIV/AIDS and what they suggest to meet these needs. In Albania, the study focuses on services provided for PLWHA and challenges that service providers encounter. In this study a quality methodology has been used. Service providers were interviewed using 20 semi-structured interviews. Data collection took place in the University Hospital “Mother Teresa” in Tirana, in the Infective Hospital Service. Data revealed that service providers refer changes in the way services are provided for PLWHA. Medical staff of Infective Hospital Service in TUHC shows a positive attitude toward these people as information and understanding about the disease has increased in the last few years. This institution has constantly sought to raise awareness and inform other professionals, family members, relatives and PLWHA themselves about this disease. There are a lot of difficulties that medical service providers face during their work with PLWHA such as: inability of PLWHA and their family members to understand and really evaluate their disease’s level, convincing PLWHA on an emergent check-up of their partner, decrease of therapy success due to diagnosis in late stages of the disease, lack of information and low level of voluntary check-ups. Today’s challenge is not only improving the quality, but also reformulating the way medical services are provided, so as to complete social and psychological aspects of health.